2011
DOI: 10.1080/02640414.2011.605163
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic comparison of the preferred and non-preferred foot punt kick

Abstract: Kicking with the non-preferred leg is important in Australian Football and becoming important in the rugby codes. The aim of this study was to examine differences between preferred and non-preferred leg kicking in the drop punt kick. Seventeen elite Australian Football players performed kicks with the preferred and non-preferred leg. Optotrak Certus collected kinematic data of the kick leg and pelvis (200 Hz) from kick leg toe-off until ball contact. Foot speed, knee and shank angular velocity at ball contact,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
4
31
2
Order By: Relevance
“…Previous studies have reported dynamic balance asymmetry during soccer specific tasks that explained differences between the preferred and the non-preferred leg (23). Therefore, our results are in agreement with previous studies indicating that kicking with the preferred leg is generally faster compared with the non-preferred leg (4,5,7,24). This was attributed a lower amount of work done on the shank (5), a lower knee muscle moment and angular impulse (7) and hip and pelvis movement control deficiencies when using the nonpreferred leg (24).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies have reported dynamic balance asymmetry during soccer specific tasks that explained differences between the preferred and the non-preferred leg (23). Therefore, our results are in agreement with previous studies indicating that kicking with the preferred leg is generally faster compared with the non-preferred leg (4,5,7,24). This was attributed a lower amount of work done on the shank (5), a lower knee muscle moment and angular impulse (7) and hip and pelvis movement control deficiencies when using the nonpreferred leg (24).…”
supporting
confidence: 83%
“…Therefore, our results are in agreement with previous studies indicating that kicking with the preferred leg is generally faster compared with the non-preferred leg (4,5,7,24). This was attributed a lower amount of work done on the shank (5), a lower knee muscle moment and angular impulse (7) and hip and pelvis movement control deficiencies when using the nonpreferred leg (24). Further, bilateral leg differences in knee strength have been previously reported (25).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…An understanding of these asymmetries and establishment of the level of asymmetry in healthy individuals is important to avoid potential injury (Knapik, Bauman, Jones, Harris, & Vaughan, 1991) and aid in the monitoring of rehabilitation programmes. Knowledge of the kinematic and kinetic characteristics of the weaker or lesser skilled limb is also important in guiding skill development and enhancing performance (Ball, 2011). Kinematic and kinetic asymmetries in healthy individuals have been observed at the ankle, knee and hip during walking and running tasks by several authors (Bredeweg, Buist, & Kluitenberg, 2013;Exell, Irwin, Gittoes, & Kerwin, 2012;Korhonen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These results partly contradict findings from previous dynamic kicking analyses in 5 highly skilled male under-17 players (Nunome, Ikegami, et al, 2006) and in 7 skilled male players (Dorge et al, 2002) No inter-limb differences in the ground reaction and support leg forces were observed in the two types of kicks as previously observed in Australian football (Ball, 2011). However, the delays in the dominant limb kicks across the various groups are an important result of this study.…”
Section: Discussioncontrasting
confidence: 57%